From Innovation to Implementation: A Qualitative Study of Kushinagar District Sugarcane Farmers' Technological Experiences - Chaturvedi, Pratibha; Vatta, Lalita (Indian Journal of Extension Education, 2026)
As information and communication technologies and precision agriculture instruments are integrated, agricultural management techniques are being enhanced. Through improved input applications, communication across various hardware and datasets, and reduced production costs, this integration intends to improve the sustainability of the sugarcane crop production system. Many sugarcane farmers, especially smallholders, continue to face low profitability, increased input prices, labour shortages, and limited benefits from institutional and digital innovations despite consistent research investment and technical advancements. The research tried to understand sugarcane-growing farmers' viewpoints and experiences about digitalization and challenges in sugarcane farming. In the Kushinagar district of Uttar Pradesh, exploratory-descriptive qualitative research was carried out at the Deoria Sugarcane Committee's Jaura Bazar Centre "A" between October 2023 and January 2025. A pre-tested semi-structured guide was used to conduct in-depth, in-person interviews with purposively recruited twenty-four sugarcane producers. Interviews were audio recorded, verbatim transcribed, and subjected to thematic analysis using NVivo 15. Results show significant discrepancies between farmers' lived experiences, extension services, and agricultural research. Technical innovations like online slip generation, digital payment systems, and digitization have increased operational efficiency and transparency. Adoption was hampered by low digital literacy, limited access to advanced technology, insufficient extension assistance, and poor institutional coordination.